Research on Linked Open Government Data and Application - Yuanming Yuan; Chanle1 Wu; Haojun Ai (Dianxin kexue)
Open government data（OGD）is growing steadily and it has been a vital communication channel between government and citizens. Government data published by linked data technology can promote transparency and even improve reuse rate of data. The paper describes the related concepts, publishing principles and advantages of linked government data. And then it deeply analyzes technology architecture which includes expression layer, compiling layer, interlinking, and browse/query layer on the basis of related concepts. Following it summarizes applications of linked government data in USA, UK and so on developed countries. Finally, it gets a view of applications and challenges of linked government data in China smart city construction.